Nuclear Translocation of the p75 Neurotrophin Receptor Cytoplasmic Domain in Response to Neurotrophin Binding - Frade, José M. (J Neurosci, 2005)
The intracellular domain of the p75 neurotrophin receptor (p75(ICD)) can be released by γ-secretase in response to the previous activation of α-secretase by phorbol esters. However, ligand-dependent release of p75(ICD) has yet to be described. We show here that nerve growth factor can induce the release of p75(ICD) and facilitate its translocation to the nucleus in a γ-secretase-dependent manner. This effect was observed in RN22 schwannoma cells cultured under serum-free conditions, as well as in Schwann cells, and it was mimicked by other neurotrophins, such as brain-derived neurotrophic factor or neurotrophin-3. Unlike other known examples of regulated intramembrane proteolysis, ligand-dependent release of p75(ICD) did not need the previous activation of α-secretase. These results suggest that nuclear translocation of p75(ICD) may represent a novel neurotrophin-mediated signaling pathway.